2009
DOI: 10.1001/archinternmed.2009.371
|View full text |Cite
|
Sign up to set email alerts
|

ALLHAT Findings Revisited in the Context of Subsequent Analyses, Other Trials, and Meta-analyses

Abstract: he Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) is reevaluated considering information from new clinical trials, meta-analyses, and recent subgroup and explanatory analyses from ALLHAT, especially those regarding heart failure (HF) and the association of drug treatment with new-onset diabetes mellitus (DM) and its cardiovascular disease (CVD) consequences. Chlorthalidone was superior to (1) doxazosin mesylate in preventing combined CVD (CCVD) (risk ratio [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…As well, the CHARM trials revealed a higher rate of doubling of serum creatinine in 82 (6%) candesartan-treated versus 47 (4%) placebo-treated patients (p = 0.002) [99,100]. Additionally, the ALLHAT study demonstrated that among the diabetics studied, more patients in the ACEI lisinopril group progressed to ESRD, when compared to the diuretic chlorthalidone group (25/1,563 vs. 26/2,755, p = 0.05, RR 1.74, 95% CI 1.00–3.01) [101,102]. Furthermore, Jones et al [8] in 2005, after a thorough analysis of the US ESRD population growth, concluded that there was an ESRD epidemic here in the USA, and that the pace of the US ESRD epidemic outpaced the growth of the diabetes mellitus epidemic.…”
Section: The Association Of Aki With Raas Blockade In Generalmentioning
confidence: 99%
“…As well, the CHARM trials revealed a higher rate of doubling of serum creatinine in 82 (6%) candesartan-treated versus 47 (4%) placebo-treated patients (p = 0.002) [99,100]. Additionally, the ALLHAT study demonstrated that among the diabetics studied, more patients in the ACEI lisinopril group progressed to ESRD, when compared to the diuretic chlorthalidone group (25/1,563 vs. 26/2,755, p = 0.05, RR 1.74, 95% CI 1.00–3.01) [101,102]. Furthermore, Jones et al [8] in 2005, after a thorough analysis of the US ESRD population growth, concluded that there was an ESRD epidemic here in the USA, and that the pace of the US ESRD epidemic outpaced the growth of the diabetes mellitus epidemic.…”
Section: The Association Of Aki With Raas Blockade In Generalmentioning
confidence: 99%
“…Very interestingly, the worse renal outcomes in the ALLHAT and CHARM‐overall trials with lisinopril and candesartan, respectively, barely received but glancing mention in the various publications (5,30). Even post hoc analyses of these RCTs have consistently and continually failed to address these concerns of potential drug treatment‐related nephrotoxicity (31). For example, the CHARM trials demonstrated a higher rate of doubling of serum creatinine in 82 (6%) candesartan‐treated vs. 47 (4%) placebo‐treated patients (p = 0.002) (5).…”
mentioning
confidence: 99%
“…Correspondingly, the ALLHAT data demonstrated that among diabetics, more patients in the lisinopril group, progressed to ESRD, when compared with the chlorthalidone group – 25/1563 vs. 26/2755, p = 0.05, RR 1.74, 95% CI (1.00–3.01) (30). Recently, we had called the ALLHAT authors to task in a recent editorial comment published in the Archives of Internal Medicine as to why this very important aspect of their findings barely received any mention in the original ALLHAT publication and in subsequent post hoc reports (31).…”
mentioning
confidence: 99%
“…Surprisingly, all the major studies were performed using higher hydrochlorothiazide doses or hydrochlorothiazide in combination with other antihypertensive agents, so little or no evidence exists for the efficacy of low-dose hydrochlorothiazide in hypertension and cardiovascular disease. The Anti-hypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT), one of the major studies showing equivalent efficacy of diuretics and other antihypertensives, was performed with chlorthalidone, which seems to be more effective than hydrochlorothiazide 41,42. Furthermore, hydrochlorothiazide at higher doses whereby its efficacy might be comparable with that of other antihypertensives, shows many adverse effects, including electrolyte imbalance (hypokalemia, hyponatremia), insulin resistance, and hyperuricemia, making it inappropriate as monotherapy 43.…”
Section: Use Of Aliskiren-hydrochlorothiazide In Hypertensionmentioning
confidence: 99%